A MicroRNA-29 Mimic (Remlarsen) Represses Extracellular Matrix Expression and Fibroplasia in the Skin - Gallant-Behm, Corrie L; Piper, Joseph; Lynch, Joshua M; Seto, Anita G; Hong, Seok Jong; Mustoe, Thomas A; Maari, Catherine; Pestano, Linda A; Dalby, Christina M; Jackson, Aimee L; Rubin, Paul; Marshall, William S (Journal of investigative dermatology, 2019)
MicroRNA-29 (miR-29) negatively regulates fibrosis and is downregulated in multiple fibrotic organs and tissues, including in the skin. miR-29 mimics prevent pulmonary fibrosis in mouse models but have not previously been tested in the skin. This study aimed to identify pharmacodynamic biomarkers of miR-29 in mouse skin, to translate those biomarkers across multiple species, and to assess the pharmacodynamic activity of a miR-29b mimic (remlarsen) in a clinical trial. miR-29 biomarkers were selected based on gene function and mRNA expression using quantitative reverse transcriptase polymerase chain reaction. Those biomarkers comprised multiple collagens and other miR-29 direct and indirect targets and were conserved across species; remlarsen regulated their expression in mouse, rat, and rabbit skin wounds and in human skin fibroblasts in culture, while a miR-29 inhibitor reciprocally regulated their expression. Biomarker expression translated to clinical proof-of-mechanism; in a double-blinded, placebo-randomized, within-subject controlled clinical trial of single and multiple ascending doses of remlarsen in normal healthy volunteers, remlarsen repressed collagen expression and the development of fibroplasia in incisional skin wounds. These results suggest that remlarsen may be an effective therapeutic to prevent formation of a fibrotic scar (hypertrophic scar or keloid) or to prevent cutaneous fibrosis, such as scleroderma.